An Ethnographic Study of the Moral Experiences of Children with Cancer in New Delhi, India - Justine M. Behan; Ramandeep Singh Arora; Franco A. Carnevale; Sameer Bakhshi; Bani Bhattacharjee; Argerie Tsimicalis (SAGE Publishing, 2021)
There is a paucity of research examining children's experiences with cancer in India. Childhood ethics is an emerging field, focusing on the moral dimension of children's experiences, to promote children's participation in their health care. A focused ethnography, using a moral experience framework, was conducted to better understand children's participation in decisions, discussions, and actions in three oncology settings in New Delhi, India. We interviewed key informants, retrieved key documents, and conducted semi-structured interviews and participant observations with children. All 22 children demonstrated interest in varying aspects of their cancer care. Certain factors facilitated or impeded their participation. Some children became distressed when they lacked information about their treatment or were not given opportunities to enhance their understanding. The results advance our understanding of the moral experiences of children with cancer in India for healthcare professionals, policy makers, families, and interested others.